Raízes nefastas do pensamento geográfico no brasil: meio, raça e nação em Oliveira Vianna (1920-1933) - Cirqueira, Diogo Marcal (Geosaberes, 2018)
The purpose of this paper is to analyze the discussions of the Brazilian thinker Oliveira Vianna (1883-1951) about race and environment in the Brazilian society. It seeks to understand how the author tries to equate the two problems involving a formation of a "developed" and "civilized" Brazilian nation at the beginning of 20 th century: the population mostly composed by "inferior race" (blacks, Indians and mestizos) and the determinations imposed by the torrid and degenerating tropical environment. Participating of a series of debates on a national project for Brazil, which begins with the formation of the Primeira República [First Republic] and the post-abolition of slavery and that reaches the Estado Novo [New State], Vianna saw in the resolution of the race and environment issues - by "the modern science " - a viable way for the country. Believing in "aryan" superiority, the author emphasizes the need to insert in the Brazilian territory a population from Europe. Producing a geographical discourse, the author establishes discussions on the man-environment relationship and makes a proposal of a regional planning for the rational allocation of “aryans types” in the Brazilian natural regions. It is important to understand the Vianna’s geographical discourse because he later influenced a set of geographers who sought to discuss the regional differences and the population in Brazil.